PROBLEMATIKA PENGUATAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN DARING - Naima, Naima; Lessy, Zulkipli (ILJ: Islamic Learning Journal, 2024)
The implementation of strengthening character education during this pandemic is very difficult, especially during the current online learning period.  This is because learning is done online where there is a lack of direct interaction between students and teachers. This study aims to see how strengthening character education through online learning. This research is a type of qualitative research, data collection methods using observation instruments, documentation, and interviews with teachers and students. Data analysis by reducing data, presenting data, triangulating data, and drawing conclusions. The first research result, Strengthening character education through online learning is by using the 2013 curriculum by referring to Presidential Regulation Number 87 of 2017 which contains religious character values, independence, nationalism, and mutual cooperation. Then second, instilling character values by modeling role models or examples of good deeds. And third, through extracurricular activities